SOFTWARE EDUCATIONAL RESOURCES AS A MEANS OF STUDYING - Novikov, Aleksey; Abdulkadirov, Umalt; Pivneva, Svetlana; Polkovnikov, Alexey; Pertsev, Vladimir (Revista Inclusiones, 2020)
The mathematization of economic sciences, which is observed today, in some cases poses the problem not only of new content but also of a completely new structure, which requires specific means of studying economic and mathematical disciplines for its solution. The article presents an analysis of studies on various aspects of the use of software educational resources as a means of studying economic and mathematical disciplines at university. Based on the results of a pedagogical experiment, the effectiveness of using software educational resources (for example, Mathcad) in the process of training future economists in the study of economic and mathematical disciplines has been verified. It is concluded that the introduction of software educational resources to the educational process improves the training of future economists and affects the methodology of teaching economic and mathematical disciplines at all levels.